Communicating National Image through Development and Diplomacy The Politics of Foreign Aid (Palgrave Studies in Communication for Social Change, 2018)
This edited collection draws upon interdisciplinary research to explore new dimensions in the politics of image and aid. While development communication and public diplomacy are established research fields, there is little scholarship that seeks to understand how the two areas relate to one another. However, international development doctrine in the US, UK and elsewhere increasingly suggests that they are integrated-or at the very least should be-at the level of national strategy. This timely volume considers a variety of cases in diverse regions, drawing upon a combination of theoretical and conceptual lenses that combine a focus on both aid and image. The result is a text that seeks to establish a new body of knowledge on how contemporary debates into public diplomacy, soft power and the national image are fundamentally changing not just the communication of aid, but its wider strategies, modalities and practices.